Effects of Anisotropic Turbulent Ocean on Propagation of Asymmetric Bessel-Gaussian Beam - Lin Yu; Zhecheng Zhang; Yixin Zhang; Lifa Hu (IEEE Photonics Journal, 2024)
Aiming at the propagation of asymmetric vortex beam, we investigate the spreading and wander characteristics of asymmetric Bessel-Gaussian beam in oceanic turbulence. Based on the cross-spectral density and Wigner distribution function of beam field, the theoretical expressions of spreading factor and beam center displacement are established to evaluate spreading and wander. The anisotropic turbulent condition is adopted to analyze turbulence impacts with more generality. The turbulence dominated by salinity fluctuation with lower anisotropy, larger temperature dissipation and smaller kinetic energy dissipation induces more beam spreading and wander. As for asymmetric Bessel-Gaussian beam, the increment of asymmetry can improve beam directionality. Besides, smaller beam scale but larger Gaussian waist radius, vortex order and beam wavelength also mitigate spreading and wander. The investigations are instructive for the underwater applications of asymmetric vortex beams.